Genetic space of radial plant growth - Greb, Thomas (Nature plants, 2019)
Radial growth of plants is one of the most prominent processes for generating biomass and the long-term sequestration of carbon dioxide on Earth. Now, the concerted action of a large set of transcription factors on the regulation of the process has been investigated.